COVID-19 pneumonia complicated by bilateral pneumothorax: A case report. (2020) - Shirai, Tsuyoshi; Mitsumura, Takahiro; Aoyagi, Kei; Okamoto, Tsukasa; Kimura, Moyu; Gemma, Taku; Shigematsu, Takaaki; Takahashi, Junichi; Azuma, Seishin; Yoshizuka, Riku; Sasaki, Hirokazu; Urushibata, Nao; et al.
Abstract: Background: Pneumothorax is a rare but life-threatening complication associated with pneumonia caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Case presentation: Informed consent was obtained from the patient himself.A 50-year-old man presented with a 9-day history of fever, cough, and dyspnoea. He was diagnosed with coronavirus disease 2019 (COVID-19) pneumonia and was admitted to the Medical Hospital, Tokyo Medical and Dental University. Chest CT showed diffuse patchy ground-glass opacities (GGOs). His state of oxygenation deteriorated, and mechanical ventilation was initiated on day 4 after admission (12th day from onset). He improved gradually and was weaned from ventilation on day 15. Sudden onset of bilateral pneumothorax occurred on day 21 with severe respiratory failure, and chest CT revealed pneumatocele formation on both lower lobes. Conclusions: Pneumothorax is a notable complication in cases of severe COVID-19 pneumonia, especially in those who require positive-pressure ventilation.